(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2020)
Cancer is one of the most prevalent diseases worldwide and the natural products could be a source of bioactive compounds. Passiflora mucronata (PM) belongs to a very known vegetal genus, although, there are no studies about cytotoxic activity or isolated compounds. Different extracts from PM were obtained by liquid-liquid partition (P), Soxhlet (Sox) and supercritical fluid (SFE1-5) extraction techniques, being compared concerning their yields, chemical profile and cytotoxicity. The Sox extracts showed the highest yields (6.03%: hexane; 2.51%: dichloromethane) followed by SFE (from 4.34 to 1.63%) and partitions (1.06 and 2.26%). The hexane partition (HP) showed the best cytotoxic activity against K562 cell line (IC50 = 18.72 µg.mL-1). From HP, the following compounds were identified and analysed its cytotoxic activities: β-amyrin (IC50 = 3.92 µg.mL-1), β-sitosterol (IC50 = 3.37 µg.mL-1), stigmasterol (IC50 = 3.31 µg.mL-1) and oleanolic acid. Stigmasterol induced about 75% of K562 total apoptosis. The compounds were tested against MA-104 cell line and the selective index (SI) attributed (SI >10 for all compounds). This indicates good selectivity to K562 cell line at the expense of MA-104. This is the first time, identifying those compounds to PM.